Hygiene, sanitation and the soil transmitted helminths (STH) infection among elementary school students in West Lombok - . Rahmawati; . Soeyoko; Sri Sumarni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
The prevalenses of soil transmitted helminths (STH) infection in Lombok are relatively high. It isclosley associated with poor environmetal hygiene, non healthy sanitation status, poverty andimproper health services. The highest prevalences is normally observed in elementary school children.The aim of this study was to evalaute the relationship between hygiene, sanitation and STH infectionamong elementary school children in West Lombok. An observational study with cross-sectionaldesign was performed involving 197 elementary school children in Terong Tawah Village, LabuapiSub District, West Lombok District and 197 children in Ampenan, Mataram City as control. Thestool specimen of the children were collected and processed using Kato-Katz technique. Hygieneand sanitation of each subject that consisted nail hygiene, hand washing, using footwear, latrine,clean water availability, house floor, soil around the house were taken by questionnaire and directobservation. The result showed that the prevalences of STH among elementary school children inTerong Tawah (81.7%) was higher than that in Ampenan (12.7%).Trichuris trichiurawas thepredominant helminth both in Terong Tawah (36.0%) and Ampenan (7.0%) followed byA.lumbricoides(20.4% in Terong Tawah and 4.5% in Ampenan). The mix infections betweenT.trichiuraandA. lumbricoidesamong the children in Terong Tawah (24.4%) and Ampenan (1.0%)were also found. A significant relationship between hygiene and sanitaion i.e. nail cleaniness, washinghands, contaminated soil around the house and STH infection among elementary school children inTerong Tawah and Ampenan (p<0.05). In conclusion,there is a significant relationship betweenpersonal hygiene, environmental sanitation and STH infections among elementary school children.